Design, synthesis, biological evaluation and molecular dynamics of LAR inhibitors. (June 2021) - Sun, Ying-Zhan; Wu, Jing-Wei; Du, Shan; Ma, Yang-Chun; Zhou, Liang; Ma, Ying; Wang, Run-Ling
Graphical abstract: Highlights: The pharmacophore model, virtual screening, fragment replacement make the design of compounds more accurate. Most of the desired compounds exhibited better inhibitory activity than the reference compound. The findings could provide useful insights for developing novel potent LAR inhibitors. Abstract: In this study, firstly, the pharmacophore model was established based on LAR inhibitors. ZINC database and drug-like database were screened by Hypo-1-LAR model, and the embryonic compound ZINC71414996 was obtained. Based on this compound, we designed 9 compounds. Secondly, the synthetic route of the compound was determined by consulting Reaxys and Scifinder databases, and 9 compounds (1a-1i ) were synthesized by nucleophilic substitution, Suzuki reaction and so on. Meanwhile, their structures were confirmed by 1 H NMR and 13 C NMR. Thirdly, the Enzymatic assays was carried out, the biological evaluation of compounds 1a-1i led to the identification of a novel PTP-LAR inhibitor 1c, which displayed an IC50 value of 4.8 μM. At last, molecular dynamics simulation showed that compounds could interact strongly with the key amino acids LYS1350, LYS1352, ARG1354, TYR1355, LYS1433, ASP1435, TRP1488, ASP1490, VAL1493, SER1523, ARG1528, ARG1561, GLN1570, LYS1681, thereby inhibiting the protein activity. This study constructed the pharmacophore model of LAR protein, designed small-molecule inhibitors, conducted compound synthesis and enzyme activity screening, so as to provide a basis for searching for drug-capable lead compounds.